PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS VII MTs NURUL HASANAH KUBU I KECAMATAN PEKAITAN TAHUN PELAJARAN 2015/2016 - ', Johan; Sayuti, Irda; Syafii, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on Observations of teaching biology at MTS as Nurul Hasanah STRONGHOLD I Sub Pekaitan Year 2014/2015, Lessons that every time there are symptoms of learning students are always backwards when process study underway, always ignoring anything that is submitted by the teacher, when in the host group activities, students do not want to work together in groups, smart students who do not want to interact with students who are weak. So that the interest of students in learning Biology still less. One way to improve student learning outcomes is by, using a model of learning, cooperative type STAD (Studet Team Achicvement Division) where learning is expected to attract the interest of students in learning Biology can developing self-reliance students, liveliness, discipline and courage of students students in expressing his opinion, so that student learning outcome increases. This research aims to improve the learning results of IPA students with the application of cooperative learning model of type Student Teams Achievement Division (STAD) Class VII MTsNurul Hasanah Stronghold I Sub Pekaitan Year 2015/2016 Lessons. This research was conducted in March-April 2016. The subject of research is the grade VII MTsNurul Hasanah Stronghold I Sub Pekaitan amounted to 21 people. Parameters measured were the result of student learning that consists of absorption and learning students individually and activity of students. The average absorbance students in cycle I, namely 74.28 (good) and cycle II of the value increases to daily repeats is 80.00 (good). students can study in cycle I, namely 80.95% with an average score of 74.28 and cycle II increased to 95.24% with an average score of 80.00. Group Award at the cycle I, 5 group predicate excellent increases in cycle II, 1 Group 4 and group both predicate predicate excellent. Learning activities of students in cycle I, namely 80.20 (good) increased in cycle II became 88.69 (very good). From the results it can be concluded that the application of the cooperative learning Model of type Student Teams Achievement Division (STAD) can improve the learning results of IPA Student Class VII MTs Nurul Hasanah Stronghold I Sub Pekaitan Year 2015/2016 Lessons.Key words: Cooperative Learning, Learning Outcomes, Kooperati type of Student Teams Achievement Division (STAD)